Mathematics teachers' and student teachers' attitudes towards mathematics teaching in comparison - Būdienė, Virginija (Lietuvos matematikos rinkinys, 1999)
This article deals with the study on attitudes of Lithuanian mathematics teachers and student teachers towards math education. The objective of the study is to determine the level and differences of basic conceptions of Lithuanian math teachers and students, and to compare with conceptions of Estonian and Finnish mathematics  teachers. The research is based upon the typology of concepts introduced by J. Dionne (1984). The common math education culture of teachers and student teachers is discovered. The discussion on revealed similarities and differences is presented.